ZOOTECHNIC CHARACTERISTICS OF MODERN POPULATIONS OF MUGALZHAR HORSE BREED - Iskhan Kairat Zhaleluly; Kalashnikov Valery Vasilievich; Akimbekov Amin Richardovich; Mongush Sayana Darzhaevna; Demin Vladimir Aleksandrovich; Rzabayev Tolybek Serikbayevich; Nesipbayeva Aigul Kadirovna; Zhilkybaeva Meruert Malikovna; Zhikishev Yerlik Kaliaskerovich (Scientific Journal of Pedagogy and Economics, 2019)
The modern structure of the Mugalzhar horse breed consists of three intrabreed types - Embensky, Kulandinsky, Kozhamberdinsky (till 2009 - Saryarkinsky), six lines and 55 families. Live weight of stallions - 560 kg, mares - 520 kg, slaughter yield - 55-60%, yield of colts - 80-90%, milkiness of mares - up to 2000 l. Horses of Mugalzhar breed are distinguished by good health, excellent adaptability to year-round pasture maintenance. The stallions of the Mugalzhar horse breed have an average live weight of 493.5 - 538.4 kg, mares - 452.7- 469.3 kg. Body measurements in stallions of Kozhamberdinskyintrabreed type were 148.9 - 153.1 - 186.9 - 20.0 cm, of Kulandinskyintrabreed 144.9 - 151.6 - 181.9 - 19.9 cm and Embensky 145.8 - 160.7 - 184.7 - 19.8 cm. Adult mares of the Kozhamberdinsky type have a height in the withers of 145.1 cm, an oblique body length of 152.5 cm, a chest girth of 180.2 cm and a metacarpus girth of 19.4 cm. The Kozhamberdinsky and Embensky mares showed an average body measurement of 143.8 - 149.9 - 179.3 - 19.1 cm and 144.7 - 155.2 - 180.8 - 18.9 cm. The improvement of the breeding and productive qualities of Mugalzhar horses is carried out in order to accumulate and consolidate especially valuable economic useful traits inherent in each breeding type and the creation of a new meat and dairy breed. The biological features of Kozhamberdinskyintrabreed type are: the ability of stallions throughout the year to maintain high fatness and even at the end of the breeding period to have higher standards. Mares are distinguished by high fecundity: 85-90 colting for 100 heads and pronounced maternal instinct. Even for the first time, the females that have become stubborn almost never throw foals. The colting, usually (up to 80.0%), occurs in the predawn hours.